Learning by developing a satellite navigation simulator - AYDIN, SERKAN (My University, 2011)
This article describes a methodology to explain and understand Satellite Navigation concepts by developing simulators in the Marmara University, Technical Education Faculty, Electronics and Computer Education Department (MUTEFEC) Istanbul. At present, senior students of MUTEFEC take graduation projects interested in their professional skills. In addition some students have got developing projects related with Global Positioning System (GPS)/Galileo (EU Satellite Navigation System). In this study; to help students and accelerate their perceptions while building their project, a teaching concept for simulator-based project developing issues in computerized environment supports the possibility of distance learning as well as a computer-aided teaching is presented. © 2009 Wiley Periodicals, Inc.
Keywords: GPS; learning by doing; project-based education; simulation; teaching methodology